2021
DOI: 10.1136/bmjopen-2020-047543
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of hyperbaric oxygen therapy for moderate-to-severe ulcerative colitis: a protocol for a systematic review and meta-analysis

Abstract: IntroductionUlcerative colitis (UC) is a type of inflammatory bowel disease, and 62% of patients with UC felt that it is difficult for them to live a normal life. Furthermore, some researches have shown that about 15% of patients with UC undergo at least one extreme clinical course in their lifetime, and 10%–30% of patients with UC oblige colectomy. Although many investigations have demonstrated that HBO2 has a beneficial impact on UC treatment, a systematic review and meta-analysis are unavailable. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…14 Based on all the biochemical effects mentioned above, HBOT has been proven to be safe and effective either alone or as an adjunct method in treating various diseases, with few side effects. 15,16 According to the Undersea and Hyperbaric Medicine Society (UHMS), HBOT is approved for the following indications; carbon monoxide poisoning, crushing traumas, compartment syndrome, cyanide intoxication, gas gangrene, decompression sickness, compromised skin graft, central retinal artery occlusion, osteomyelitis, delayed radiation injury, necrotizing soft tissue infection, air or gas embolism, actinomycosis, acute thermal burns, sensorineural hearing loss, anemia, and diabetic wounds. 15 Possible adverse effects of HBOT are as follows: barotraumatic middle ear injury, sinus damage, oxygen poisoning-which can cause pulmonary failure, pulmonary fluid congestion, seizures or myopia-claustrophobia, hypoglycemia in diabetics, dizziness, and weakness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Based on all the biochemical effects mentioned above, HBOT has been proven to be safe and effective either alone or as an adjunct method in treating various diseases, with few side effects. 15,16 According to the Undersea and Hyperbaric Medicine Society (UHMS), HBOT is approved for the following indications; carbon monoxide poisoning, crushing traumas, compartment syndrome, cyanide intoxication, gas gangrene, decompression sickness, compromised skin graft, central retinal artery occlusion, osteomyelitis, delayed radiation injury, necrotizing soft tissue infection, air or gas embolism, actinomycosis, acute thermal burns, sensorineural hearing loss, anemia, and diabetic wounds. 15 Possible adverse effects of HBOT are as follows: barotraumatic middle ear injury, sinus damage, oxygen poisoning-which can cause pulmonary failure, pulmonary fluid congestion, seizures or myopia-claustrophobia, hypoglycemia in diabetics, dizziness, and weakness.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 According to the Undersea and Hyperbaric Medicine Society (UHMS), HBOT is approved for the following indications; carbon monoxide poisoning, crushing traumas, compartment syndrome, cyanide intoxication, gas gangrene, decompression sickness, compromised skin graft, central retinal artery occlusion, osteomyelitis, delayed radiation injury, necrotizing soft tissue infection, air or gas embolism, actinomycosis, acute thermal burns, sensorineural hearing loss, anemia, and diabetic wounds. 15 Possible adverse effects of HBOT are as follows: barotraumatic middle ear injury, sinus damage, oxygen poisoning-which can cause pulmonary failure, pulmonary fluid congestion, seizures or myopia-claustrophobia, hypoglycemia in diabetics, dizziness, and weakness. 17,18 Although, despite all the aforementioned therapeutic effects of HBOT, most of the available evidence regarding its efficiency is based on small-scale randomized clinical trials (RCTs), and retrospective studies.…”
Section: Introductionmentioning
confidence: 99%
“…HBOT can enhance healing in ischemic colonic anastomosis by improving the local anaerobic environment [ 12 ]. Similarly, a few case reports have indicated that HBOT can improve clinical manifestations of IBD, although the underlying mechanisms have not been explored [ 13 , 14 ]. Based on these findings, we hypothesize that HBOT will benefit patients with CD by modulating the composition of the host gut microbiota, thereby influencing the efficacy of biologic agents.…”
Section: Introductionmentioning
confidence: 99%